Agricultural practices for mechanical weed control with small-scale maize farmers and willingness to pay a hire service: technical report - López Gómez, Jesús Antonio; Loon, Jelle J. van (International Maize and Wheat Improvement Center, 2023)
Exploring the use of innovative tools that facilitate the execution of tasks is a fundamental step towards mechanization, however, it is also important to know the acceptance level of these solutions by potential users. Additionally, the business models generation must be accompanied by the assessment of current needs based on the typology of producers, the agroecological conditions and the agricultural infrastructure of the region. For this reason, in this study the level of acceptance and the farmer’s willingness to pay to a service provider for the use of different tools compared to conventional tools in different areas of the states of Oaxaca, Chiapas, Campeche and Yucatán were determined. A total of 106 surveys were carried out, with 25% women participation and an average age of 45 years. The average plot size of the interviewed producers was 2 ha with yields around 2 ton/ha. The results show that in these regions there is a lack of adequate technology for weed control, with manual methods (machete, hoe, etc.) or a combination of these with the application of chemical products being the most used. In general, the farmer’s willingness to pay to a service provider varies from 150 – 600 pesos per workday and the highest level of acceptance for these services was reported in the state of Campeche.